2021
DOI: 10.1287/mnsc.2019.3562
|View full text |Cite
|
Sign up to set email alerts
|

The Demotivating Effects of Communicating a Social-Political Stance: Field Experimental Evidence from an Online Labor Market Platform

Abstract: Despite a recent surge in corporate activism, with firm leaders communicating about social-political issues unrelated to their core businesses, we know little about its strategic implications. This paper examines the effect of an employer communicating a stance about a social-political issue on employee motivation, using a two-phase, preregistered field experiment in an online labor market platform. Results demonstrate an asymmetric treatment effect of taking a stance depending on whether the employee agrees o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 68 publications
6
44
0
Order By: Relevance
“…Second, while social CSR initiatives have the potential to create a favorable image among subsets of stakeholders, these initiatives are perceived as being less focused, less verifiable, and thus more prone to agency costs (Mishra and Modi 2016). Moreover, recent research shows that consumers and shareholders do not always agree with the direction of social CSR, with some viewing such actions as an alienating form of activism (Burbano 2021;Hydock, Paharia, and Blair 2020;Yashoda, Warren, and Beck 2020). Therefore: H 3 : Having an environmental rather than a social focus in a CSR initiative enhances the positive effect of corrective and compensating CSR initiatives and mitigates the negative effect of cultivating CSR initiatives.…”
Section: The Moderating Effect Of Firms' Csr Reputation and Csr Focus...mentioning
confidence: 99%
“…Second, while social CSR initiatives have the potential to create a favorable image among subsets of stakeholders, these initiatives are perceived as being less focused, less verifiable, and thus more prone to agency costs (Mishra and Modi 2016). Moreover, recent research shows that consumers and shareholders do not always agree with the direction of social CSR, with some viewing such actions as an alienating form of activism (Burbano 2021;Hydock, Paharia, and Blair 2020;Yashoda, Warren, and Beck 2020). Therefore: H 3 : Having an environmental rather than a social focus in a CSR initiative enhances the positive effect of corrective and compensating CSR initiatives and mitigates the negative effect of cultivating CSR initiatives.…”
Section: The Moderating Effect Of Firms' Csr Reputation and Csr Focus...mentioning
confidence: 99%
“…All non-theoretical works build on samples derived from the US-market. Although Burbano (2021) does include responses from participants outside the USA, the author is addressing a US-oriented political debate in connection with a US-based company. Moreover, the publication does not account for any cultural differences between the respondents in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…They show that both are positively influenced by political alignment (Brown et al , 2020; Mkrtchyan et al , 2020). These conceptions, however, are opposed by Burbano (2021), who found a demotivating effect of CEO activism that opposed the viewpoints of their company’s workforce but no motivating effect of CEO activism in favour of these statements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research suggests that strategic leaders engaging in social activism could be in a no-win situation. Burbano (in press) found that an employer taking a stance on a social issue demotivates employees who disagree with the stance and has no motivating effect on employees who agree with the stance. Alternatively, Chatterjee and Toffel (2018) discuss “the risk of silence, which may be viewed as a sign of tacit approval.” This risk is reflected in recent accusations from activists that silence on racial inequality, for example, amounts to complicity in it.…”
Section: Strategic Leadership Research On Activism and Social Issuesmentioning
confidence: 98%